Fraud Triangle Analysis Detects Fraudulent Financial Statements Using A Fraud Score Model from BUMN Bank 2012-2022 - Adha, Almandio; Indrayani, Emmy (Ilomata International Journal of Management, 2024)
This study delves into anti-fraud measures within Indonesia's banking sector, specifically focusing on four state-owned banks (BUMN). Against a backdrop of financial challenges faced by entities like Krakatau Steel and Jiwasraya, the government and Financial Services Authority (OJK) introduced internal controls to rebuild public trust. However, concerns arise with the establishment of BUMN holding companies, consolidating top executives. Public trust significantly influences BUMN performance, leading to reinforced banking regulations by OJK. This research employs SPSS Version 25 to scrutinize the impact of pressure, opportunity, and rationalization on financial statement fraud in state-owned banks from 2012 to 2022. The study's noteworthy findings reveal that financial stability, external pressure, financial targets, and rationalization do not effectively detect financial statement fraud, while the nature of the industry and ineffective monitoring demonstrate the potential to identify such fraud. These insights contribute to a comprehensive understanding and improved prevention and management strategies for financial statement fraud in Indonesia's state-owned banking sector, emphasizing the influence of the fraud triangle.